2016
DOI: 10.1155/2016/1381760
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Serums CCL11, CCL17, CCL26, and CCL27 and Disease Severity in Patients with Urticaria

Abstract: Background. Chemokines may be involved in the pathogenesis of urticaria, but their correlation with disease severity as well as eruption type is unclear. Objectives. The aim of this study was to explore the expression of chemokines in patients with urticaria. The association between disease severity and levels of chemokines was analysed. Materials and Methods. Serums CCL11, CCL17, CCL26, and CCL27, D-dimer, C-reactive protein, and total IgE were measured in 51 patients with urticaria and in 25 healthy control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Since a diagnostic test measuring functionally active autoantibodies has not yet been made available, the diagnosis of autoimmune urticaria (AIU) is still obscure [9]. Interestingly, chemokines such as CCL17, CCL26, and CCL27 were significantly increased in patients with AIU in comparison to other forms of CU and correlated with disease severity [91].…”
Section: Mast Cell Activationmentioning
confidence: 99%
“…Since a diagnostic test measuring functionally active autoantibodies has not yet been made available, the diagnosis of autoimmune urticaria (AIU) is still obscure [9]. Interestingly, chemokines such as CCL17, CCL26, and CCL27 were significantly increased in patients with AIU in comparison to other forms of CU and correlated with disease severity [91].…”
Section: Mast Cell Activationmentioning
confidence: 99%
“…1 The long-lasting course and distressing symptoms have a grave impact on life quality. [3][4][5][6][7][8][9] The activity of T cells is largely dependent on the differentiation of T0 cells into subtypes of CD4+ T-helper (Th) cells, such as Th1, Th2, Th17 and Th22 cells, which can be further grouped based on distinct cytokine profiles. Increasing evidence indicated that inflammation and unbalanced immunity play critical roles in the generation and promotion of the recurrent symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Inflammatory cells and the cytokines released in the peripheral circulatory micro-environment are proposed to determine the immune response in CSU. [3][4][5][6][7][8][9] The activity of T cells is largely dependent on the differentiation of T0 cells into subtypes of CD4+ T-helper (Th) cells, such as Th1, Th2, Th17 and Th22 cells, which can be further grouped based on distinct cytokine profiles. 10 A complex network of cytokines released by the Th cells is involved in various autoimmune and allergic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells show both inhibitory and stimulatory effects on antibody production by mast cells (6). Of particular relevance to the current study are the recent findings revealing that Th2/ Th17 cytokines, transcription factors and Th2 chemo kines are upregulated or elevated in CSU patients' skin lesions, plasma and serum, respectively (7)(8)(9)(10). Accordingly, Th2 and Th17 pathways may be involved in the pathogenesis of CSU, and CCL17 and IL-17 can serve as serum markers of Th2 and Th17 inflammation, respectively.…”
mentioning
confidence: 70%
“…An additional factor related to CSU is CCL17, or thymus activation-regulated chemokine (TARC). CCL17 is a well-recognized Th2 chemokine that has been reported to be increased in the sera of CSU patients as Lu et al (9) showed that serum concentrations of CCL17 were significantly increased in 24 patients with CSU as compared to 25 healthy controls. Moreover, in the present study, we report that serum levels of CCL17 were significantly increased in the active phase of CSU and significantly decreased in the remission phase.…”
Section: Discussionmentioning
confidence: 99%